From the shade into the sun: exploring pride and shame in students with special needs in Finnish VET - Ryökkynen Sanna; Maunu Antti; Pirttimaa Raija; Kontu Elina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This paper reports on a study of the dynamics of social emotions and social bonds between students and class teachers by analysing the narratives of students receiving intensive special support in the Finnish vocational education and training (VET) system. Pride refers to a strong and safe involvement in interaction, and shame implies intimidated social bonds. The analysis is based on abductive content analysis for which Greimas' actant model worked as an analysis tool. We found some students showing high respect to their teachers who acted as senders setting the objects for students' studying. Pride is based on the students' experiences in achieving the objects, thereby pleasing their teachers and secondly on their ability to see positive development in their social belonging. The students who experienced feelings of shame did not perceive themselves as being subjects of positive development, but their special needs overshadowed their social relationships. They found it difficult to see approving and benevolent senders and receivers which could be interpreted as an explicit source of shame. The results concern not only individual teachers' pedagogical practices and ways of interaction, but also the whole VET system which addresses competence and effective individual study paths rather than social belonging and communality.